Factors Affecting Capital Expenditure with Economic Growth as a Moderating Variable - Zuhroh, Shufia (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to determine the effect of Banten Province Regencies/Cities: Regional Original Income, General Allocation Funds, and Special Allocation Funds on Capital Expenditures. For the years 2017–2021, all of the regencies and cities in Banten Province make up the study's population. This study's data analysis technique is multiple linear regression analysis, which uses pooled data and the Eviews 9 software. The study's findings demonstrated the concurrently significant effects of regional original income, general allocation funds, and special allocation funds on capital expenditure. While General Allocation Funds and Special Allocation Funds have no discernible impact on capital expenditures, Regional Original Income has a positive and significant effect on them. While DAU in response to capital expenditures cannot be moderated, PAD and DAK can be by the moderating variable of economic growth.